Implementasi Sistem Penerangan Jalan Umum Berbasis Smart LED untuk Meningkatkan Penerangan di Wilayah Kinagara Regency - Ramadan, Dadan Nur; Anwar, Radial; Hafidudin, Hafidudin (Abdibaraya, 2025)
This community service program aims to address the issue of inadequate street lighting in RT.04 Kinagara Regency, a residential complex with minimum street lighting facilities. The proposed solution is the installation of Smart Lights based on the Internet of Things (IoT) to enhance road lighting within the housing area. Each light can have its intensity adjusted manually or automatically through light and motion sensors. These lights are connected to a Wi-Fi-based IoT network, enabling remote monitoring and control. The installation of Smart Lights will be carried out at critical points in the area, involving residents in the installation process, supervision, and training for maintenance. Through technical training, the residents of Kinagara Regency are empowered to actively participate in the system's maintenance and management, ensuring long-term sustainability. This program seeks to improve safety, comfort, and energy efficiency in RT.04 Kinagara Regency while reducing street lighting operational costs. Based on testing, street lighting improved by 7 Lux compared to previous levels, and a questionnaire revealed 100% of respondents stated that the community service program met their expectations.Keywords: smart light, internet of things, operating costs